Blood-brain-barrier modeling with tissue chips for research applications in space and on Earth - Yau, Anne; Jogdand, Aditi; Chen, Yupeng (Frontiers in Space Technologies, 2023)
Tissue chip technology has revolutionized biomedical applications and the medical science field for the past few decades. Currently, tissue chips are one of the most powerful research tools aiding in in vitro work to accurately predict the outcome of studies when compared to monolayer twodimensional (2D) cell cultures. While 2D cell cultures held prominence for a long time, their lack of biomimicry has resulted in a transition to 3D cell cultures, including tissue chips technology, to overcome the discrepancies often seen in in vitro studies. Due to their wide range of applications, different organ systems have been studied over the years, one of which is the blood brain barrier (BBB) which is discussed in this review. The BBB is an incredible protective unit of the body, keeping out pathogens from entering the brain through vasculature. However, there are some microbes and certain diseases that disrupt the function of this barrier which can lead to detrimental outcomes. Over the past few years, various designs of the BBB have been proposed and modeled to study drug delivery and disease modeling on Earth. More recently, researchers have started to utilize tissue chips in space to study the effects of microgravity on human health. BBB tissue chips in space can be a tool to understand function mechanisms and therapeutics. This review addresses the limitations of monolayer cell culture which could be overcome with utilizing tissue chips technology. Current BBB models on Earth and how they are fabricated as well as what influences the BBB cell culture in tissue chips are discussed. Then, this article reviews how application of these technologies together with incorporating biosensors in space would be beneficial to help in predicting a more accurate physiological response in specific tissue or organ chips. Finally, the current platforms used in space and some solutions to overcome some shortcomings for future BBB tissue chip research are also discussed.